Rancang Bangun Sistem Informasi Penjualan Bahan Baku Gypsum dan Baja Berbasis Web - Monica Anita Wijaya; Sopian Aji; Fandhilah Fandhilah (Universitas Bina Sarana Informatika, 2018)
Abstract - CV Gypsum Griya Indah is a market leader distributor company in the industry of gypsum and mild steel raw materials. The sales system at this company is still manually felt to be less effective in attracting customers. By implementing information systems at Griya Indah CV Gypsum which is engaged in sales and wants to expand its marketing area through an E-commerce website. Aside from being a means of promotion, E-commerce websites can simplify the process of ordering and purchasing goods. E-commerce websites do not only act as information media but can also expand sales areas to reach all of Indonesia and internationally. For consumers, websites simplify the process of purchasing goods needed. In this study the method used is the waterfall method which describes a systematic and sequential approach to software development, starting with the specification of user needs and then continuing through several stages as follows planning, modeling, construction, and the delivery of the system to customers / users, then end with complete software support generated. By using webset as a media. Keywords: E-commerce Website, Gypsum Raw Material, Light Steel